2023
DOI: 10.3390/coatings13081357
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Investigation of Point Defects on the Thermal Conductivity and Mechanical Properties of Aluminum at Room Temperature

Abstract: The effects of point defects on the mechanical and thermal conductivity of aluminum at room temperature have been investigated based on the first-principles calculations combined with the Boltzmann equation and the Debye model. The calculated results showed the equilibrium lattice constants a0 of all REAl are larger than that of Al, and the defective formation energy Ef of all REAl is lower than that of VAl. Both a0 and Ef increase from Sc to La and then decrease linearly to Lu. The effects of solute atoms on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…Jiang et al [12] investigated the effect of point defect on the structures and mechanical properties of defective BiCuOTe, and they found that point defects improved the elastic compliance but weakened the compression resistance of BiCuOTe. Fan et al [13] suggested that Al matrix with vacancy and substitutional rare element addition presented the ductility and nonuniform. Muzy et al [14] studied the point defects by thermostimulated luminescence, and it was found that the dislocations in the specimens were pinned due to point defects, while the samples with more dislocations became more resistant to plastic deformation in Verneuil crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al [12] investigated the effect of point defect on the structures and mechanical properties of defective BiCuOTe, and they found that point defects improved the elastic compliance but weakened the compression resistance of BiCuOTe. Fan et al [13] suggested that Al matrix with vacancy and substitutional rare element addition presented the ductility and nonuniform. Muzy et al [14] studied the point defects by thermostimulated luminescence, and it was found that the dislocations in the specimens were pinned due to point defects, while the samples with more dislocations became more resistant to plastic deformation in Verneuil crystals.…”
Section: Introductionmentioning
confidence: 99%